How the Chinese E-commerce platform can utilise sustainable marketing techniques to improve brand image and influence consumer behaviour - taking example of purchasing fashion products. - Li, Yinan (2021)
This research aims to explore how Chinese e-commerce platforms can utilize sustainable marketing techniques to enhance brand image and further influence consumer purchasing behaviour. Therefore, the specific research statement of this dissertation is to comprehend how the triple bottom line principle and sustainable marketing mix can guide Chinese e-commerce platforms to develop sustainable marketing strategies, explore the impact of sustainable marketing activities on the brand image of Chinese e-commerce enterprises, and further demonstrate how Chinese e-commerce platforms adopt sustainable marketing strategies to improve customer satisfaction, trust and brand loyalty, thereby affecting consumers’ purchase intention and shopping behaviour. This study first reviews previous research on sustainable marketing and consumer behaviour in related fields and determines the research approach and direction by referring to their research results. Moreover, this study adopts the method of quantitative research to conduct an online questionnaire survey among Chinese online shopping consumers over the age of 18, and a total of 230 valid samples are collected. The research results indicate that, following the triple bottom line principle and sustainable marketing mix to develop marketing strategies will have a positive influence for the sustainable brand image of Chinese e-commerce platforms. Furthermore, the brand image established by e-commerce platforms through sustainable activities can be positively correlated with consumer purchasing behaviour by improving customer satisfaction, customer trust and brand loyalty. Therefore, the findings of this research confirm the hypothesis and verify the reliability of the proposed theoretical model. Finally, through the discussion of the research findings, specific theoretical significance and practical implications are proposed for e-commerce platforms to adopt sustainable marketing techniques to improve brand and influence consumer behaviour.